Penerapan Teknik Vokal Intonasi Dalam Menyanyikan Lagu Buku Zinuno No 232 “No Somuso Todo Ndrao - Shinta Nifati K. Zebua; Robert K A. Simangungsong; Roy J. M. Hutagalung; Testi Bazarni Zebua; Tahadodo Waruwu (LPPM Politeknik Pratama, 2023)
The aim of this research is to find out about vocal intonation techniques. Several things that must be paid attention to when singing are vocal techniques such as breathing techniques, articulation, expression and intonation and also signs of dynamics contained in the song. Intonation is the cooperation between tone, stress, duration and stops that accompany a speech, from the beginning to the last stop. This research uses qualitative research with data collection instruments, interviews and documentation. In the song No Somuso Todo Ndrao, it is sung with a tempo of MM=100 (Moderato), has 17 bars and uses quarter and eighth notes with a 6/8 time signature and there are several dynamic signs including p (piano), mf (mezzo forte), f (forte),Cresecendo( < ) Descrescendo ( > ) The researcher chose song No. 232